The provisions of apportionment of benefits and judicial apportionment in Jordanian law - Najim, Narven Fawzi (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the research is to show the apportionment that deals with the process of decompression in Jordan and provide appropriate solutions to it, which is the adaptive apportionment and the judicial apportionment, of course by following the Jordanian legislation and the judiciary of the Jordanian Court of Cassation in this regard, explaining and analyzing it to reach the desired solutions, and the research followed the legal analytical descriptive approach, and that By reviewing the texts of laws and their interpretation. And a review of court rulings related to decommunity issues, and a number of results were reached, the most prominent of which is that the Jordanian legislator included the accommodating apportionment in the fourth section of the third book in the Jordanian civil law related to the cessation of commons, although the conditioning is not considered a property apportionment and does not terminate the commonality, but rather a apportionment of benefits. The Jordanian legislator necessitated setting the temporal adjustment period, and leaving the determination of the amount of the period to the partners, each according to his share in the common money, so the period may be, for example, six months, a year or three years, and the research recommends that in the case of dissolution due to gross injustice, the law did not address The possibility of the partners owning the share of the partner who was wronged, in cash or in kind, to remove the wrongdoing. The researcher recommends the Jordanian legislator that this should be raised to avoid re- apportionment and shortening the time.